Research on the Integration Model of Art Education and Entrepreneurship in the Digital Age: Taking the Innovation of Art Examination Training Industry as an Example - Huang Ranwei (SHS Web of Conferences)
Against the backdrop of rapid development of the digital economy, the integration of art education and entrepreneurship has gradually become an important direction for education reform and industrial innovation. The widespread application of digital technology has not only changed the teaching form of art education, but also injected new vitality into entrepreneurial models. The art examination and training industry, as an important component of art education, has shown tremendous development potential and innovation space with its high degree of specialization and market orientation. However, driven by the digital wave, the art examination and training industry is also facing problems such as a single teaching mode, uneven resource allocation, and insufficient technology application. It is urgent to promote industry transformation and upgrading by integrating digital technology and entrepreneurial thinking. This article is based on the theory of digital economy and entrepreneurship, analyzing the theoretical basis of the integration of art education and entrepreneurship, and taking the art examination and training industry as the research object, systematically exploring its development status and main challenges in the digital age. At the same time, a fusion model was proposed, with intelligent teaching platforms, virtual reality technology, and blended online and offline teaching as the core, to promote innovation in teaching content and service models. In addition, this article also proposes practical paths such as strengthening policy support, promoting school enterprise cooperation, and improving resource sharing efficiency, in order to provide practical theoretical support and feasible solutions for the development of the art examination and training industry, and to provide more references and inspirations for the integration of art education and entrepreneurship.